Gestão do Processo de Recuperação das Bibliografias dos Projetos Pedagógicos dos Cursos de Graduação no Acervo da Diretoria Integrada de Bibliotecas da Universidade Federal do Maranhão - LIMA, Jousiane Leite (2024)
The bibliographic collection of the Integrated Directorate of Libraries of the Federal University of Maranhão is listed, cataloged and made available online through the Integrated System for the Management of Academic Activities, however, it does not present, so far, the possibility of generating information from the bibliographies of each UFMA course, which can be met by customizing the system through an online report. In this perspective, this research has like general objective to develop an improvement for the management of the bibliographies of the pedagogical projects of the undergraduate courses of UFMA and the management of the bibliographic collection of the institution's libraries. The methodological procedures used in this study involved applied research that resulted in a technical-technological product in the form of process improvement; qualitative research in which an analysis of the functionalities of the management systems of the studied institution was carried out; exploratory research where more information was sought about the topic studied through higher education assessment instruments; bibliographical research in the main databases, electronic magazines, physical and virtual libraries, as well as in institutional repositories of theses and dissertations and documentary research in the extraction of information in standards, resolutions, reports and internal guides of the studied institution. The results present the elaboration of the improvement that includes the customization of SIGAA, as well as the development of new functionalities in this system. It is concluded that in order to guarantee the achievement of the objective proposed in this work, it will be necessary to have the support of all actors involved in the process, as well as the University managers.